Coffee and the Risk of Lymphoma: A Meta-analysis Article - Tianjie HAN; Junshan LI; Ling WANG; Hongzhi XU (Tehran University of Medical Sciences, 2016)
Background: Coffee is implicated in the susceptibility to several cancers. However, the association between coffee and lymphoma remains unclear. This meta-analysis aimed to assess quantitatively the association between coffee and the incidence of lymphoma. Methods: A literature search was performed for cohort and case-control studies published using PubMed, Cochrane, and EMBASE databases. Studies were included if they reported relative ratios (RR) and corresponding 95% confidence intervals (CIs) of lymphoma with respect to coffee consumption. Pooled relative risk (RR) and its 95% confidence interval (CI) were calculated. All P values are two tailed Results: Seven studies met the inclusion criteria, which included three cohort and four case-control studies. Compared with did not or seldom drink coffee per day, being no significantly association between coffee and risk of lymphoma (pooled RR: 1.05, 95%CI: 0.89-1.23). In the subgroup analysis, no significant association between coffee and lymphoma risk was detected not only in different study types (cohort studies RR: 1.29; 95% CI, 0.92-1.80; case control studies RR: 0.99; 95% CI, 0.82-1.99) but also in different regions (Europe RR: 1.21; 95% CI: 0.99-1.47; USA RR: 0.85; 95% CI, 0.62-1.15; Asia RR: 1.08, 95% CI: 0.84-1.40) and coffee consumption status (≥4cups/d 1.03, 95% CI: 0.69-1.56; ＜4cups/d RR: 1.06, 95% CI: 0.89- 1.26 ). The funnel plot revealed no evidence for publication bias. Conclusion: There was no sufﬁcient evidence to support coffee consumption association with the risk of lymphoma. Further well-designed large-scaled cohort studies are needed to provide conclusions that are more definitive.